2019
DOI: 10.1186/s12966-019-0887-1
|View full text |Cite
|
Sign up to set email alerts
|

Eating behaviors and weight loss outcomes in a 12-month randomized trial of diet and/or exercise intervention in postmenopausal women

Abstract: BackgroundCertain eating behaviors are common among women with obesity. Whether these behaviors influence outcomes in weight loss programs, and whether such programs affect eating behaviors, is unclear.MethodsOur aim was to examine the effect of baseline eating behaviors on intervention adherence and weight among postmenopausal women with overweight or obesity, and to assess intervention effects on eating behaviors.Four hundred and 39 women (BMI ≥25 kg/m2) were randomized to 12 months of: i) dietary weight los… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0
6

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(51 citation statements)
references
References 50 publications
1
42
0
6
Order By: Relevance
“…6,7,37,47,66 Fourth, at the time of peer-review, the search had been over a year old and three new studies were identified. [87][88][89] The findings are briefly reported here.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…6,7,37,47,66 Fourth, at the time of peer-review, the search had been over a year old and three new studies were identified. [87][88][89] The findings are briefly reported here.…”
Section: Discussionmentioning
confidence: 78%
“…87 Mason et al found no changes in eating behavior traits relating to binge eating, uncontrolled eating, emotional eating, and restrained eating after 12 months of aerobic exercise training in postmenopausal women. 88 And Paravidino et al showed that during 2 weeks of moderate-intensity, vigorous-intensity, or no-exercise control in Brazilian Naval Academy cadets with overweight, changes in self-reported energy intake were not different among groups nor were there any changes in appetite sensations taken before and after an ad libitum cafeteria breakfast. 89 A final issue concerns the methodology of meta-analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Most nonsurgical interventions did not assess this relationship, but research with adults illustrates that this association may be significant. Multiple studies have found that adults with overweight who reported greater decrease in BE following nonsurgical weight‐loss interventions were more successful than adults who had less significant change in BE (57,65).…”
Section: Discussionmentioning
confidence: 99%
“…The postmenopausal women in Europe had the best depressive remission among the five continents. As the dietary habits of the women in various countries are different, such as the preferable diet of having soy products in Japan and Korea may cause an effect on the results of the phytoestrogens 49 . Additionally, considering the ethnic diversity in different regions, more experiments are needed to explore the specific conclusions.…”
Section: Discussionmentioning
confidence: 99%